AFCW3 Economic Update, Fall 2018 : Disrupting the Gender Divide in Mali, Chad, Niger and Guinea - World Bank Group (World Bank, Washington, DC, 2018)
Mali, Chad, Niger and Guinea have some of the lowest rates of secondary school completion in the world for girls. They also have some of the highest rates of child marriage and early childbearing. While some other countries in West and Central Africa are making rapid progress toward better educational attainment for girls and fewer child marriages, progress is uneven across the four focal countries. Among them, Guinea has achieved the largest gains over the last few decades, but progress in Chad, Mali, and Niger has been slow and in some cases inexistent. Child marriage, early childbearing, and low educational attainment hinder girls’ empowerment. This Note documents trends in these areas over time as well as their impact on other development outcomes and economic costs. Finally, policies and programs that could improve outcomes for adolescent girls are discussed.